Cellular Core Sandwich Structures for Offshore Construction - Ab Hadi, Muhamad Naqiuddin (IRC, 2016)
A new type of material system that can multifunction which is sandwich structures having open cell truss cores can be fabricated by means of reasonable deformation, assembly as well as joining processes. There are varieties of core architecting in recent days by means of wrought metal alloys using reasonable textile as well as perforated sheet methods. The design, fabrication as well as properties for these kind of structures will be study. Proposal on a new computational mechanics model has been done in order to explain the compression response of 2D cellular materials together with deliberation of microstructural development. Processing requirements in order to fabricate cellular materials is considered as a cell-growth mechanism in this modeling. Phase-field model generated the representative volume elements (RVE). For the selected RVE, finite element analysis will perform numerical simulations of compressive deformation. The limit stress as well as densification process are affected by the cell size distribution especially.